Legal basics for the functioning councilors clubs in polish voivodeships councils before the change of the polish local government law before 2018 year (Discourse of Law and Administration, 2021)
This article discusses about the councilors clubs in polish voivodeships councils. The author focuses on legal basics, which describes in detail at the two levels of legal regulation. There are regulations in the Act at the first level and the statutes of individual voivodeships at the second level. The text is divided into three main parts, which describe the different perspectives of these issues. In the introduction it is described the legal nature of the function of councilor. Author shows that the councilors provinces are working on the representative body only because they were elected. During the work in that body they have both obligations as well as rights. Associating in clubs is such a privilege. In the next part are presented research purposes: main purpose, methods and detail purposes. The first part of main text describes the sociological and legal nature of the clubs in voivodeships councils. Author shows that the clubs despite the activities in the representative bodies are not their internal organs. These are the kind of form of political councilors associations. The second part presents the legal basics for the functioning the clubs contained in the Act until 2018. Reflections are based largely on the decisions of the Constitutional Court and administrative courts. There are presented the freedom as well as its limitations in the creation of these clubs. The results of the author’s empirical research and analysis done in 2016 are presented in the third part. There are described in turn the provisions in the statutes of individual voivodeships. In the fourth part it is described current legal status of the councillor clubs in the Act. The last part describes results and cunclusions.
Keywords: local government; voivodeships councils; councillors clubs